CULTURAL EXPRESSION IN MADURESE SPOKEN SPEECH AND INDONESIAN LANGUAGE IN ELEMENTARY/MI STUDENTS IN SUMENEP - Agus Wahdian; Nyimas Robbiany Pandanarum; M. Ridwan (Jurusan Sastra Indonesia, 2020)
Purpose of this study First, describing cultural expression in spoken speech madura language and Indonesian among elementary/MI students. Second, describes the pattern of interaction and cultural expression that occurs in students with teachers, principals, and other stakeholders. This research method uses a qualitative approach that decrypts spoken speech of cultural and language expression. The type used by this study is phenomenological, which is to study the pattern of interaction process of oral speech of students as an expression of language and culture. Based on the results of research in the field in two schools namely SDN Keles and MI Miftahul Jannah speech or oral speech of students when interacting and communicating either with teachers or with fellow students, found several spoken speeches that included the cultural expression section of Madura language as the first language and Indoensia language as a second language.As the following Teachers and Students spoken speeches. Teacher: Big signs of doomsday, what? Student 1: Nabbu terompet. (H) Teacher: Drumben? (while joking). Student 2: Munculla Imam Mahdi (I).